SUBSURFACE HYDROTHERMAL ALTERATION STUDY OF SIBANGGOR TONGA AND ITS IMPLICATIONS ON THE SORIK MARAPI GEOTHERMAL CONCEPTUAL MODEL - Agna Ramadhan, Nindyan
The Sorik Marapi Geothermal Field is located on Sumatra Island and is one of the geothermal field areas in Indonesia that is already in production. The Sorik Marapi Geothermal Field will conduct COD (Commercial Operation Date) for the second unit in 2021 with a 45 MW capacity. Based on previous research, detailed and microscopic descriptions regarding the lithological characteristics and hydrothermal alteration have not been conducted or published. Therefore, research on rocks and subsurface hydrothermal alteration is essential to discover the rock condition and subsurface alteration and furthermore its implications to the geothermal conceptual model of Sorik Marapi. This study uses primary data such as rock cuttings and fluid chemistry from wells X and Y, which were drilled to 2500 mKU. In addition, this research is also assisted by secondary data such as resistivity interpretations in the forms of maps and cross-sections along with pressure-temperature curves. This research includes megascopic analysis, petrographic analysis, and spectral analysis from Analytical Spectral Devices (ASD) as methods to identify the mineral composition of rock powder samples from wells X and Y in the Sibanggor Tonga area. Furthermore, geochemical interpretation and well pressure and temperature curves analysis were also carried out. The alteration minerals that are identified throughout the wells consisted of smectite, illite, pyrite, calcite, chlorite, quartz, anhydrite, epidote, muscovite, pyrophyllite, diaspore, and alunite. The results of mineral identification are integrated with geochemical data and well pressure-temperature to determine subsurface conditions. Based on mineral identification, the rocks observed throughout well Y are pyroclastic rocks, andesite lava, and dacitic lava with argillic and propylitic alteration types and were formed in three stages. The hydrothermal alteration of well Y is predicted to form during two different regimes based on the temperature fluctuations. Minerals at shallow depths are predicted to be relict minerals. The emergence of high-temperature acid fluid is predicted to be related to the source of acidic fluid and the presence of faults. The integration of alteration minerals with geochemical data and well temperature pressure indicate that the alteration minerals at depth are formed in equilibrium conditions with the currently developing geothermal system. The reservoir zone is located approximately at 1488 mKU with a reservoir temperature of 235-260?C. The clay cap zone consists of clay alteration minerals located at 300-600 mKU.